MANAGING SUPPLY NETWORKS BASED ON THE SMART CITY CONCEPT – A REVIEW OF GOOD PRACTICES - Bielski, Bartłomiej; Drzymała, Daria (Acta Universitatis Nicolai Copernici. Zarządzanie, 2021)
The aim of the article was to present solutions of the Smart City concept, which can also have a real impact on the management of supply networks. One of the two main grounds that make up the Smart City concept are human potential and technological potential, whose components are divided into six functional dimensions. Effective and reliable city management and supply network management depends on a well-chosen strategy and methods used. Benefits and effects of city management based on the Smart City concept can be seen in the ranking of the most intelligent cities. A city has its own centre, and in the case of a supply network, such a centre can be a city that has to cooperate so that the various processes carried out by the various links in the supply chain pass through it correctly, giving mutual benefits.